The Impact of Climate Change on Wine Tourism from the Perspective of Hungarian Organic Wineries - Borbély Noémi Viktória; Keller Krisztina (EU agrarian Law)
The study aims to investigate the impact of climate change on wine tourism from the perspective of Hungarian organic wineries. During the qualitative research, we examined the perceptible signs, the positive and negative aspects of climate change and its impact on wine tourism based on the example of five organic wineries in different Hungarian wine regions. We focused on organic production and explored why the interviewees use this method and how it affects wine tourism. In addition, we examined the sustainability efforts and plans of the wineries. It can be concluded that organic wineries have perceived the effects of climate change for about 10–15 years in wine production and wine tourism; the weather has become more unpredictable. The wineries protect against adverse effects by planting other grape varieties and introducing new procedures. Climate change did not induce organic production, but sustainable management is essential for the examined companies.